Tree-ring width measurements of Douglas fir from Kaiserslautern from 1922 to 2021 - Alexander Land; Daniel Reichle (PANGAEA, 2024)
Wood samples from Douglas fir trees were taken using an increment borer. From each tree two opposing increment cores were taken at breast height. The sampled trees stood in an area of ~50x50 meters. Total ring width was measured and digitized. The resulting two radii measurements of each tree were visually synchronized and averaged to form a tree-ring series. Additionally, metadata were collected such as tree height, circumference and provenance (coastal, interior). The tree-ring data were used to investigate the resilience, resistance and recovery of the Douglas fir trees to severe drought events and to perform climate sensitivity analysis. This tree-ring dataset was part of a sampling campaign to assess the growth potential of Douglas fir trees until the year 2100. Annual tree growth variability until 2100 was modeled for Germany (including the river basins draining to Germany) with a spatial resolution of 12x12 km using regional climate projections ensemble.
In: Land, A; Reichle, D (2024): Tree-ring width measurements of living Douglas firs in Central Europe [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971943